if $J_x= \oint y^2 ds $ and $J_y= \oint x^2 ds $ and $J_{xy} = \oint xy ds $
how I can find $a$ and $b$? $$\left\{\begin{matrix} a.J_{xy}+b.J_x=-M_x\\ a.J_y+bJ_{xy}=M_y \end{matrix}\right.$$
$M_x, M_y$ are const.

Is it a right solution to find $a$ based on $b$ from one of the equations and replace its value on the other equation?

$$a=\frac{b.J_x - M_x}{J_{xy}}$$ $$b=\frac{M_y J_{xy}}{J_x J_y - M_x J_y + bJ^2_{xy}}$$


Denote the equations by $(1)$ and $(2)$ respectively. Then

$$ J_x \times (2) - J_{xy} \times (1) \implies a(J_xJ_y-J_{xy}^2) = M_yJ_x+M_xJ_{xy} \implies a=\dfrac{M_yJ_x+M_xJ_{xy}}{J_xJ_y-J_{xy}^2}$$

$$ J_{xy}\times(2) - J_y\times (1) \implies b(J_{xy}^2 - J_yJ_x) = M_yJ_{xy} + M_xJ_y \implies b=-\dfrac{ M_xJ_y+ M_yJ_{yx} }{J_yJ_x-J_{yx}^2 }$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.